2011
DOI: 10.1002/cncr.26431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low estrogen/progesterone receptor expression on survival outcomes in breast cancers previously classified as triple negative breast cancers

Abstract: Purpose To evaluate the impact of low ER/PR expression and effect of endocrine therapy on survival outcomes in HER2-negative tumors with ER/PR < 10%, previously labeled as triple negative. Methods In a retrospective review, 1257 patients were categorized according their ER/PR percentages into three groups, ER/PR <1% (Group A), ER/PR 1–5% (Group B) and ER/PR 6–10% (Group C). Kaplan-Meier product limit method was used to estimate survival outcomes. Cox proportional hazards models was used to adjust for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 33 publications
8
52
1
Order By: Relevance
“…Additionally, in our study, we used cut off values of ER, PR expression different that the current ASCO/CAP guidelines considered as positive (1%) 26 since we have shown the lack of efficacy of adjuvant endocrine therapy in patients with < 5% ER or PR expression. 27 We don't believe this influence our results on mesothelin expression. Recent studies reported an association between mesothelin expression and clinical outcomes in patients with ovarian cancer, pancreatic cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, in our study, we used cut off values of ER, PR expression different that the current ASCO/CAP guidelines considered as positive (1%) 26 since we have shown the lack of efficacy of adjuvant endocrine therapy in patients with < 5% ER or PR expression. 27 We don't believe this influence our results on mesothelin expression. Recent studies reported an association between mesothelin expression and clinical outcomes in patients with ovarian cancer, pancreatic cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 88%
“…They did report a trend for a recurrence-free survival advantage with tumors in the 6% to 10% range of staining (n = 119). In the study by Raghav et al, 6 ER results were based on central review, but the authors do not comment on whether their results arise from a single observer reviewing all cases or if any interobserver discrepancy existed in the reporting of results in the case of multiple observers. Although some might advocate raising the threshold to 6% or higher based on the data of Raghav et al, 6 doing so will not completely remove the discrepancy problems highlighted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…6 This retrospective study reported overall survival and recurrence-free survival in a large number of low-level ER-expressing tumors, including a subset of patients who received endocrine therapy, albeit with limited follow-up. Raghav et al 6 found no significant recurrence-free survival advantage at 3 years in patients with tumors that stained less than 1% (n = 897) or between 1% and 5% (n = 241), while those with ER staining between 6% and 10% (n = 119) showed a recurrence-free survival advantage trend.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data seem to indicate that the pros (therapeutic benefit) and cons (potential side effects) of giving hormonal therapies for patients with minimal ER and PR positive expression should be cautiously evaluated. In a recent study, aiming to investigate the impact of low ER and PR expression (<10%) as well as the effect of endocrine therapy on survival outcomes of 1,257 previously classified triple negative breast cancer patients, Raghav et al (Raghav et al 2012) observed that for both ER/PR 1%-5% and 6%-10% level subgroups, no prognostic utility and only a tendency for survival advantages were found, respectively. These controversial findings reveal that the application of endocrine therapy in these patients needs further investigation (Brouckaert et al 2013).…”
Section: Discussionmentioning
confidence: 99%